Parental Role in Enhancing Students’ Motivation in Islamic Religious Education - Fatmawati Fatmawati; Mulyadi Mulyadi; Reffy Ananda Rizki; Anna Ropitasari; Delvia Muharramah; Neneng (Journal of Curriculum and Pedagogic Studies (JCPS), 2025)
Parental involvement is a crucial factor in shaping students’ motivation in learning Islamic Religious Education, which emphasizes both cognitive understanding and the internalization of religious values. This study aims to analyse the role of parents in enhancing students’ motivation in Islamic Religious Education from an ecological perspective. A qualitative research approach was employed, and the study was conducted at SDN Kadusirung II, Bogor Regency. Data were collected through in depth, semi structured interviews with parents of students and an Islamic Religious Education teacher, selected using purposive sampling. The data were analysed thematically using the interactive model of data condensation, data display, and conclusion drawing. The findings indicate that parents play interconnected roles as educators, motivators, facilitators, and learning guides by monitoring learning activities, modelling positive religious behaviour, providing motivational encouragement, creating supportive learning environments, and utilizing accessible learning resources, including digital media. These roles contribute significantly to students’ enthusiasm, persistence, and positive attitudes toward learning. Despite time and academic limitations, consistent parental involvement was found to be essential in sustaining students’ learning motivation.